Technology Enhanced Learning and Teaching in Higher Education Institutions in the 21 Century: Benefits and Challenges - Matere, Audrey; Oranga, Josephine (Journal of the Kenya National Commission for UNESCO, 2025)
Modern higher education faces challenges for both learners and lecturers. While digital resources, Web 2.0 technologies, and online connectivity offer significant learning opportunities, many Virtual Learning Environments (VLEs) remain basic and fragmented. This study investigated technology-enhanced learning and teaching in Kenyan higher education institutions. Utilizing a descriptive survey design, the study involved 15 ICT staff and 1467 students from various institutions, employing stratified and purposive sampling methods. Data was collected through questionnaires and interview schedules, with quantitative analysis conducted using SPSS and qualitative data analyzed thematically. The findings reveal that technology enhances learning by providing access to information, promoting interactive and immersive experiences, fostering collaboration, and offering cost-effective resources. It also supports adaptive learning, critical thinking, and skills development. However, challenges such as limited access to technology, digital literacy gaps, high costs, data privacy concerns, and resistance to technology adoption were identified. Despite these obstacles, universities are successfully using technology to promote active learning, collaboration, and academic support, contributing to improved teaching and learning outcomes in higher education.